2018
DOI: 10.31557/apjcp.2018.19.11.3251
|View full text |Cite
|
Sign up to set email alerts
|

Marked Inhibition of Cellular Proliferation in the Normal Human Esophageal Epithelial Cells and Human Esophageal Squamous Cancer Cells in Culture by Carotenoids: Role for Prevention and Early Treatment of Esophageal Cancer

Abstract: Background:Globally Esophageal cancer is a common cancer arising from human esophageal mucosal tissue. Epidemiological studies suggest inverse correlation between carotenoid intake and incident risk of this devastating malignancy.Methods:In an effort to examine the modulatory role of carotenoids in human esophageal carcinogenesis at a cellular level, we examined the effects of α-carotene and β-carotenes, on cell proliferation and DNA synthesis in human esophageal epithelial (HEE) cells and human esophageal squ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…Blood carotenoids are a reliable biomarker of usual intake of fruits and vegetables (33,38) . Carotenoids can reduce damage from reactive oxidative species, inhibit lipid peroxidation and are involved in cellular communications that regulate proliferation and apoptosis (39,40) . Inverse associations between dietary or circulating levels of carotenoids and mortality have been previously observed (23,41) , suggesting the potential benefits of carotenoids for optimal health and prevention of disease.…”
Section: Discussionmentioning
confidence: 99%
“…Blood carotenoids are a reliable biomarker of usual intake of fruits and vegetables (33,38) . Carotenoids can reduce damage from reactive oxidative species, inhibit lipid peroxidation and are involved in cellular communications that regulate proliferation and apoptosis (39,40) . Inverse associations between dietary or circulating levels of carotenoids and mortality have been previously observed (23,41) , suggesting the potential benefits of carotenoids for optimal health and prevention of disease.…”
Section: Discussionmentioning
confidence: 99%
“…Most of the in vitro studies recently focused on anti-carcinogenic mechanism of beta-carotene in lung, liver and blood cells. In some animal studies, alfa-carotene demonstrated a higher suppressor activity on liver, lung, skin and colon carcinogenesis compared to beta-carotene ( 30 ).…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that the molecular protective mechanisms of carotenoids in isolated human cell culture include: ( 1 ) stopping the cell cycle in G1/G0 phase by decreasing cycline D1 levels; ( 2 ) apoptosis induction downregulating survivin levels; ( 3 ) increase in cellular gap junction communication and ( 4 ) angiogenic effect through modulation of various cytokines including decreased interleukin-6 (IL-6), IL-1b, tumour necrosis factor alpha and granulocyte-macrophage colony-stimulating factor levels and increased IL-2 and TIMP metallopeptidase inhibitor 1 (TIMP-1) levels ( 30 , 31 ). Chemotherapeutic effects via similar mechanisms have been reported for all-trans retinoic acid (ATRA), another vitamin A analog ( 32 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other mechanisms underlying the anticancer effects of this carotenoid in esophageal squamous carcinoma cells include up-regulation of PPAR-γ and down-regulation of cyclin D1 and COX-2 expression [384]. Likewise, β-carotene, in combination with α-carotene, demonstrated a strong antiproliferative activity as well as a reduction in DNA synthesis in esophageal cancer cells [385]. In relation to hepatic cancer, a mixture of different carotenoids, including αand β-carotene, lycopene, LUT, and BCX, evidenced a higher antimetastatic activity than individual carotenoids in human hepatocarcinoma SK-Hep-1 cells [386].…”
Section: Human Studiesmentioning
confidence: 99%